Кримінальне переслідування княгині Марії Любомирської: епізод з життя 1915 р. (на підставі матеріалів Центрального державного історичного архіву України у м. Київ) - Якимчук, О.О. (Історичний архів. Наукові студії, 2013)
Серед джерел з дослідження польської аристократії, зокрема шляхти Рівненського
повіту Волинської губернії, є матеріали справи 698, опису 2, фонду 315 ЦДІАУ у Києві
про притягнення до кримінальної відповідальності княгині Марії Любомирської під час
відвідання військовополонених австрійських офіцерів у госпіталі м. Рівного 6 березня
1915 р. Вона звинувачувалася у: застосуванні фізичної сили до вартового госпіталю,
відвіданні військовополонених у невідповідний час, зневазі до чергового лікаря.
7(20) травня 1915 р. провадження у справі було припинене, оскільки звинувачення,
вказане в 1-му пункті, – недоведене, а звинувачення, викладені у інших пунктах, – не
відповідають складу злочинів.
Ця справа є яскравим прикладом того, що шляхетське походження не вберігало осіб
від кримінальних переслідувань. Навпаки, належність до польської аристократії навіть
на початку ХХ ст. могла спричинити упереджене ставлення при оцінці тих чи інших дій
її представників. Среди источников к исследованию польской аристократии, в частности шляхты
Ровенского уезда Волынской губернии, есть материалы дела 698, описания 2, фонда
315 ЦГИАУ в г. Киеве о привлечении к криминальной ответственности княгини Марии
Любомирской во время посещения военнопленных австрийских офицеров в госпитале
г. Ровно 6 марта 1915 г. Она обвинялась в: применении физической силы к караульному
госпиталя, посещении военнопленных в несоответствующее время, пренебрежении к
дежурному врачу.
7(20) мая 1915 г. производство в деле было прекращено, поскольку обвинение,
указанное в 1-ом пункте, – недоказано, а обвинения, указанные в других пунктах, – не
соответствуют составу преступлений.
Это дело есть примером того, что шляхетское происхождение не оберегало лиц
от криминальных преследований. Наоборот, принадлежность к польской аристократии
даже в начале ХХ века могла вызвать предвзятое отношение при оценке тех или иных
действий ее представителей. Volyn Joining to the Russian Empire by the second (1793) and third (1795) divisions of the
Rich Pospolita has made it possible to realize the aspirations of the Russian autocracy in ruling
the region, particularly by displacing the privileged hitherto layers from the top positions in all
spheres of life.
One way to achieve the aim were sustainable lawsuits in civil matters the subject of which
was the gentry’s land seizing from the Volyn Chamber property, the Orthodox church
institutions, rural communities and other landowners, as well as funds collection from the
gentry-defendants on the basis of debt receipts or bills.
The criminal gentry proceedings were numeral. Massive criminal cases were opened on
nobles charges of the commitment to rebellion. However, in the early twentieth century the
Gentry fall under the Empire law enforcement scrutiny.
Thus, it is not surprising is that to determine social position of the elite of Polish society
aimed both domestic and foreign researchers.Історичний архів
184
However, a comprehensive study of the Polish aristocracy, including Volyn province Rivne
district gentry during the late XVIII – early ХХ centuries may be done by studying both published
and unpublished documents.
Therefore, the purpose of this publication is the introduction to the scientific use of archival
materials that illuminate the life of the Volyn region gentry in the in the 1915 during the First
World War.
One of archival sources are the materials of the case 698, description 2, of Archives fund
315 describing the prosecution of the representative of one of the most powerful noble families
Princess Mary Lubomirska while visitting imprisoned Austrian officers in Rivne hospital on the
6th of March 1915. The princess was accused of:
1) the use of physical force to the prisoners hospital guard, which prevented the Princess to
enter the room
2) visiting prisoners at inappropriate hours (at 8 pm), which is in violation of the hospital rules
( prisoners visiting was allowed between 15 and 17 hours).
3) neglecting the doctor, by communicating exclusively Polish in excessive tone and
returning to the prisoners room.
However, while studying the investigation materials the chief of the military judiciary unit
under the chief of the Southwestern Front armies on the 7(20) May 1915 found it necessary
stop the proceedings. He concluded that the charge specified in the first paragraph is unproven,
and accusations contained in other items – those that do not meet the crime.
Therefore, this case is a prime example of the fact that the gentry origin couldn’t protect from
criminal prosecutions. On the contrary, belonging to the Polish aristocracy, even in the early
twentieth century could cause prejudice in the evaluation of certain actions of its members.